Approximation properties of multivariate exponential sampling series - Kurşun, S.; Turgay, M.; Alagöz, O.; Acar, T. (Carpathian Mathematical Publications, 2021)
In this paper, we generalize the family of exponential sampling series for functions of n variables and study their pointwise and uniform convergence as well as the rate of convergence for the functions belonging to space of -uniformly continuous functions. Furthermore, we state and prove the generalized Mellin-Taylor's expansion of multivariate functions. Using this expansion we establish pointwise asymptotic behaviour of the series by means of Voronovskaja type theorem.